2021
DOI: 10.25299/sportarea.2021.vol6(2).6248
|View full text |Cite
|
Sign up to set email alerts
|

Are hemoglobin and volume oxygen maximum (vo2max) relevant each other?

Abstract: The support for recording achievements in sports achievements, two of which are the ability to enter oxygen (O2) into the lungs and further the ability to take up this oxygen so that it can be utilized in the process of providing energy. The second function of O2 is to transport carbon dioxide (CO2) through respiration. These two processes are carried out simultaneously at least between the respiratory cycle and its close relationship with hemoglobin. Hemoglobin is part of the blood which has a function to bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
(38 reference statements)
1
4
1
Order By: Relevance
“…This is in line with research conducted by Pompano and Haas (2019), which found that iron supplementation increased endurance performance at submaximal and maximum training intensity (VO2 peak) in IDNA women. However, this is different from the results found by Wati (2021), which found that the level of hemoglobin (Hb) in the blood with the value of maximum oxygen volume (VO2 max) was not related or uncorrelated so that hemoglobin does not contribute to increases or decreases in values maximum oxygen volume. Iron is an essential component of hemoglobin which is bound to red blood cells.…”
Section: Iron Tablets and Maximum Oxygen Volume (Vo2 Max)contrasting
confidence: 77%
“…This is in line with research conducted by Pompano and Haas (2019), which found that iron supplementation increased endurance performance at submaximal and maximum training intensity (VO2 peak) in IDNA women. However, this is different from the results found by Wati (2021), which found that the level of hemoglobin (Hb) in the blood with the value of maximum oxygen volume (VO2 max) was not related or uncorrelated so that hemoglobin does not contribute to increases or decreases in values maximum oxygen volume. Iron is an essential component of hemoglobin which is bound to red blood cells.…”
Section: Iron Tablets and Maximum Oxygen Volume (Vo2 Max)contrasting
confidence: 77%
“…The crux of the Boltzmann problem is that the collision term on the right-hand side of the equation is nonlinear. 3 The BGK approximation is a simplification of the Boltzmann equation. Mohamad et al generalized it to the following formula to replace the BGK approximation of the Boltzmann equation:…”
Section: Table Tennis Trajectory Simulation By Fluid Mechanics Methodsmentioning
confidence: 99%
“…ρ is the macroscopic density of the liquid. O(β 3 ) is infinitely few. In this paper, the Boltzmann equations are discretized in space, velocity, and time according to the BGK approximation.…”
Section: Table Tennis Trajectory Simulation By Fluid Mechanics Methodsmentioning
confidence: 99%
“…Normal haemoglobin levels make the process of transporting oxygen into the tissues more optimal. 48 A review of research has provided evidence that high-intensity exercise has a positive effect on oxygen levels. The mechanism of high intensity exercise is that the heart, lungs and muscular system are forced to work hard and one of the effects is an increase in the maximum amount of oxygen.…”
Section: Acknowledgementmentioning
confidence: 99%